Method for the bonding and debonding of substrates

The method simplifies substrate bonding and separation by using a radiation-permeable connecting layer and a soluble layer that dissolves with electromagnetic radiation, addressing inefficiencies in existing methods and ensuring a clean substrate surface.

KR103041388B1Active Publication Date: 2026-10-30EV GRP E THALLNER GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020267003935
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2015-11-02
Filing Date
2016-10-24
Publication Date
2026-10-30
Estimated Expiration
2036-10-24

AI Technical Summary

Technical Problem

Existing methods for bonding and separating substrates are complex and require multiple steps, often involving high temperatures and chemical processes, which can be inefficient and require additional cleaning steps.

Method used

A method utilizing a connecting layer that is permeable to electromagnetic radiation and a soluble layer that dissolves upon interaction with radiation, allowing for direct separation of substrates without significant heating or chemical cleaning, using a laser to reduce adhesion between the substrates.

Benefits of technology

Enables efficient and simplified bonding and separation of substrates with minimal heating and no chemical cleaning, ensuring a clean substrate surface and reducing the complexity of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112026015903572-PAT00002_ABST
    Figure 112026015903572-PAT00002_ABST
Patent Text Reader

Abstract

The present invention relates to a method for bonding a product substrate (2) to a carrier substrate (5) through a connecting layer (4), wherein a soluble layer (3) is applied between the connecting layer (4) and the product substrate (2), a) the soluble layer (3) is soluble due to interaction with electromagnetic radiation from a radiation source, and b) the connecting layer (4) and the carrier substrate (5) are at least permeable to electromagnetic radiation. Additionally, the present invention relates to a method for separating a product substrate (2) from a carrier substrate (5) bonded to a product substrate (2) through a connecting layer (4), wherein a soluble layer (3) is applied between the connecting layer (4) and the product substrate (2), a) the soluble layer (3) is soluble due to interaction with electromagnetic radiation from a radiation source, and b) the connecting layer (4) and the carrier substrate (5) are at least permeable to electromagnetic radiation. In addition, the present invention relates to a corresponding product substrate-to-carrier substrate junction.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for bonding a product substrate to a carrier substrate through a connecting layer according to claim 1, a method for separating a product substrate from a carrier substrate bonded to a product substrate through a connecting layer according to claim 2, and a product substrate-to-carrier substrate bonding portion according to claim 9. Background Technology

[0002] Numerous methods for debonding / separating two substrates (product substrate and carrier substrate) are known from the prior art. Most methods utilize a so-called bonding adhesive to achieve a temporary bond between the two substrates, which can be restored. Bonding adhesives are typically polymers, particularly thermoplastic resins.

[0003] The first method for temporary bonding consists of coating the entire surface of the substrate. The second substrate is connected to the first substrate by a bonding operation. Separation, that is, the separation of the two substrates, is performed by a shearing process at an elevated temperature. This temperature is preferably above the glass transition temperature of the bonding adhesive. Due to the applied shear force, the two substrates can be moved relative to each other in a very slow process, and thus separated from each other.

[0004] A second method for temporary bonding consists of treating specific surface areas of the carrier substrate so that the bonding effect between these surface areas and the bonding adhesive is minimized, specifically so that this effect does not appear. A very small, untreated surface area is left excluding these specially treated surface areas. This high-adhesion surface area is typically a periphery circular ring several millimeters thick. After this special treatment, the entire surface of the carrier substrate is coated with bonding adhesive. Then, a conventional bonding operation is performed. The separation operation is generally performed by chemical means, which separates the rim area of ​​the bonding adhesive and consequently reduces the adhesive force between the carrier substrate and the bonding adhesive. After that, the carrier substrate can easily lift the product substrate.

[0005] Another method for separating two substrates from each other consists of applying a special soluble layer on a transparent carrier substrate before applying a bonding adhesive. Since the carrier substrate is permeable to certain electromagnetic radiation, photons can access the soluble layer without obstruction. The photons cause changes in the soluble layer and reduce the adhesion to the bonding adhesive. This method is described in WO2014058601A1, in which a UV laser is irradiated onto the soluble layer from the inside of the carrier substrate to perform a reaction that allows the carrier substrate to be separated from the product substrate and separates the bonding adhesive from the carrier substrate. The problem to be solved

[0006] A prerequisite of the present invention is to propose a method and apparatus in which an optimized process of bonding and unbonding / separation is achieved and subsequent method steps are simplified. means of solving the problem

[0007] This condition is satisfied by the features of claims 1, 2 and 9. Advantageous embodiments of the invention are given in the dependent claims. Any combination of at least two features provided in the specification, claims and / or drawings corresponds to the configuration of the invention. In a given numerical range, values ​​within the indicated limiting range are also disclosed as boundary values ​​and are claimed in all combinations.

[0008] The present invention is based on the concept that a product substrate-to-carrier substrate bond can be achieved, wherein two substrates can be connected through a connecting layer that is at least primarily permeable to electromagnetic radiation, and a flexible layer designed to dissolve as a result of interaction with electromagnetic radiation from a radiation source is arranged on the product substrate and the connecting layer.

[0009] In this regard, the method of the present invention can be implemented during bonding by applying the following features / steps:

[0010] a) The soluble layer is soluble due to interaction with electromagnetic radiation from a radiation source, and

[0011] b) The connection layer and the carrier substrate are at least permeable to electromagnetic radiation.

[0012] In this regard, the method of the present invention can be implemented during bonding by applying the following features / steps:

[0013] a) The soluble layer is soluble due to interaction with electromagnetic radiation from a radiation source, and

[0014] b) The connection layer and the carrier substrate are at least permeable to electromagnetic radiation.

[0015] In this regard, the device of the present invention may be implemented particularly by the following features:

[0016] a) The soluble layer is soluble due to interaction with electromagnetic radiation from a radiation source, and

[0017] b) The connection layer and the carrier substrate are at least permeable to electromagnetic radiation.

[0018] In particular, an independent principal concept of the present invention consists of using a bonding adhesive (connecting layer) having a low absorption coefficient in the wavelength range of electromagnetic radiation, particularly lasers. The absorption coefficient, particularly the linear absorption coefficient, is preferably standardized by mass density. The mass absorption coefficients obtained accordingly can be compared with one another.

[0019] Mass absorption coefficients are from the NIST X-ray attenuation database for some organic compounds and elements regarding Roentgen radiation ( http: / / www.nist.gov / pml / data / xraycoef It can be obtained from ). Since the mass absorption coefficient depends very strongly on wavelength, for some pure elements and some organic compounds, especially polymers, the wavelength range and mass absorption coefficient range are indicated as follows.

[0020] ingredient Energy range Wavelength range Mass absorption coefficient range 1 MeV Nm cm 2 / g lead 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5 polystyrene 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5 PMMA 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5 Teflon 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5 MyLAR 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5 polyethylene 10 -6 -10 2 1240-1,2*10 -5 10 -2 -10 5

[0021] In the NIST X-ray attenuation database, the value range for the mass absorption coefficient is 10 -3 MeV to 10 2 The MeV definition range is displayed. This definition range is UV range 10 -5 Since it falls within the defined range of MeV, the mass absorption coefficient cannot be directly read in the UV range. However, the value range of mass absorption coefficients for the elements carbon, nitrogen, and oxygen within the desired UV range is known from US5965065A. In particular, carbon is a major component of organic polymers. Although the mass absorption coefficient of a compound cannot be automatically derived from the mass absorption coefficients of its pure components, the value range of the mass absorption coefficient of the compound can nevertheless be estimated. From all this data, the mass absorption coefficient for the compound according to the present invention is 10 -6 -10 2 MeV to about 10 -2 -10 5 cm 2It can be recognized that it varies within the defined range of energy / g. This is a value range of 7 times the power of 10. US5965065A also states that the mass absorption coefficient of carbon is 1000 cm⁻¹ 2 / g to 10 -6 cm 2 It indicates that the change is within a factor of 10 to 100 eV from 1000 eV to 100 eV. Additionally, the absorption edge for carbon can be recognized at approximately 300 eV. All this data indicates that small changes in energy or wavelength range can cause large changes in the absorption characteristics of the material. Therefore, for all possible materials according to the present invention, it is not possible to achieve or provide any objective of specifying a single value for the mass absorption coefficient for a single material. Accordingly, according to the present invention, a soluble layer can be applied to the product substrate instead of the carrier substrate. Due to the low absorption of electromagnetic radiation through the bonding adhesive, sufficient photons reach the soluble layer to initiate a separation or disbonding operation. The present invention also relates to a plant and method for separating or disbonding two substrates with the help of an electromagnetic photon source, in particular a laser. In particular, the present invention is based on the concept of directing or focusing electromagnetic radiation onto the soluble layer to reduce adhesion between the product substrate and the carrier substrate. Electromagnetic radiation is transmitted through the bonding adhesive connecting the two substrates without heating.

[0022] The concept of the present invention is accordingly composed of a specifically matched combination of a bonding adhesive, electromagnetic radiation, and a soluble layer.

[0023] In particular, one advantage of the present invention is configured so that a soluble layer can be applied to a product substrate. Thus, the soluble layer is located between the product substrate and the connecting layer. When adhesion is reduced by irradiation of the soluble layer, particularly due to electromagnetic radiation, particularly a laser, the product substrate can be separated directly from the bonding adhesive, particularly automatically. Therefore, the product substrate is preferably removed from the bonding adhesive immediately after separation, so no chemical cleaning is required.

[0024] The soluble layer is preferably designed to be completely destroyed and, in particular, sublimated during the adverse effects of the present invention. Electromagnetic radiation interacts with the electrons of the material. Interaction occurs because the alternating electromagnetic field can cause electrically charged electrons to vibrate. The positively charged core has a much larger mass and is more inert with respect to electrons. Therefore, the movement of the core is largely neglected. The alternating electromagnetic field can produce different physical effects in solids, particularly molecules, independently of frequency. Since the innovative idea of ​​the patent specification relates to polymers, the physical effects will now be described specifically for molecules, particularly polymers. Under certain conditions, a molecule or part of a molecule can absorb photons and convert photon energy into vibrational and / or rotational and / or potential energy. To ensure that such energy conversion can occur, the photons must have a specific frequency. The newly generated energy state can be degraded again by the emission of photons of the corresponding wavelength. This constant absorption and emission of photons and the associated energy conversion and energy distribution among the individual degrees of freedom of the molecule are subject to statistical processes, which are not discussed in detail here. Primarily, electromagnetic radiation in the microwave and infrared ranges stimulates molecules to rotate. It is desirable for electromagnetic radiation in the infrared range to stimulate molecules to vibrate. There are two types of vibration: valence (stretching?) vibration and deformation vibration. The former ensures that two atoms of a molecule vibrate along the bond axis, while the second type of vibration is a vibration occurring between at least three atoms of a molecule where the bonding angle changes.

[0025] Photons of electromagnetic radiation in the UV wavelength range already possess such high energy that they can ionize molecules by lifting individual electrons in the molecular structure to higher molecular orbitals or by separating electrons from molecular bonds. The excited electrons are, in particular, valence electrons and are therefore electrons in the outermost molecular orbitals. The removal of core electrons clearly requires higher photon energies, particularly in the Roentgen wavelength range. Transmission is greatest in these wavelength ranges, where there may be no excitation of electrons from the highest occupied molecular orbital (HOMO) to the lowest occupied molecular orbital (LUMO). Since it is impossible to lift electrons from the HOMO to the LUMO orbital, photons cannot interact with electrons; thus, photons pass unhindered through solids, particularly polymers, most preferably bonding adhesives. Therefore, molecular orbital theory already provides a hint regarding the permitted chemical structure of the bond according to the present invention.

[0026] Radiation sources, especially photon sources

[0027] According to the present invention, a photo source is used particularly as a radiation source. Thus, it is predominantly, preferably entirely, a photo source. The photo source emits, particularly at least predominantly, preferably entirely, within one or more of the following wavelength ranges:

[0028] Microwave, 300 mm - 1 mm,

[0029] Infrared, especially

[0030] o Near-infrared, 0.78 µm - 3.0 µm,

[0031] o Mid-infrared, 3.0 µm - 50 µm,

[0032] o Far infrared rays, 50 µm - 1000 µm,

[0033] Visible light 380 nm - 780 nm,

[0034] UV light, especially

[0035] o Near UV light 360 nm - 315 nm,

[0036] o Medium UV light, 315 nm - 280 nm,

[0037] o Original UV light, 280 nm - 200 nm,

[0038] o Vacuum UV, 200 nm - 100 nm

[0039] o Extreme UV light, 121 nm - 10 nm

[0040] X-ray light, 0.25 nm - 0.001 nm.

[0041] The following wavelength range is preferred: 1000 µm to 10 nm, more preferably 780 nm to 100 nm, most preferably 370 nm to 200 nm.

[0042] In addition, a source capable of generating two different wavelength ranges may also be used. In this case, all conditions of the present invention apply to each individual wavelength. A combination of UV light and IR light may be particularly desirable. IR light is provided primarily to heat the soluble layer, and UV light is provided primarily to break the covalent compound. In this combination, the bonding adhesive of the present invention must contain low absorption in both wavelength ranges.

[0043] According to the present invention, a coherent photo source is preferred, and at least primarily, preferably entirely, particularly a microwave source, preferably a laser, or a laser composed of a coherent photo source for visible light, UV light, and X-ray light is preferred. The photo source may be operated in a continuous mode or (preferably) a pulsed mode. The pulse time is particularly less than 1 s, preferably less than 1 ms, more preferably less than 1 µs, most preferably less than 1 ns. The time between two consecutive pulses is preferably greater than 1 ms, more preferably greater than 100 ms, most preferably greater than 1 s.

[0044] The wavelength of the photon source is selected so that the photon stream can be radiated at least mainly, preferably completely, through the connecting layer, particularly through the bonding adhesive, without any significant loss due to absorption.

[0045] The absorption of photons through the connecting layer is particularly less than 50%, preferably less than 25%, more preferably less than 10%, most preferably less than 1%, and most preferably less than 0.1%. Accordingly, the transmission of photons through the connecting layer may be greater than 50%, preferably greater than 75%, more preferably greater than 90%, most preferably greater than 99%, and most preferably greater than 99.9%. The absorption value refers to the layer thickness selected according to material properties and requirements for the product wafer.

[0046] In particular, the characteristics of the connecting layer and the photon source / electromagnetic radiation are controlled and / or selected (particularly by selecting the material itself) so that the connecting layer is not significantly heated. In particular, heating is less than 50°C, preferably less than 25°C, more preferably less than 10°C, most preferably less than 1°C, and most preferably less than 0.1°C. In particular, heating can be substantially eliminated by using a photon source in an electromagnetic wavelength region that does not stimulate the vibrational or rotational degrees of freedom of the molecules of the connecting layer. To prevent heating, it is preferable to use electromagnetic light in the UV-VIS wavelength range in combination with a connecting layer that is transparent to UV-VIS.

[0047] A radiation source according to the present invention, in particular an electromagnetic photon source, will be described as a preferred embodiment, in this case a laser. Instead of a laser, the aforementioned radiation source may be used.

[0048] Quantitative analysis of the transparency of a solid, particularly a polymer, preferably a connecting layer according to the present invention is performed using a UV-VIS spectrometer. A UV-VIS spectrum is a graph showing the transmission of photons of a specific wavelength as a function of wavelength.

[0049] carrier substrate

[0050] The most important factor regarding preferred embodiments of the carrier substrate is transparency to the wavelength of the laser used (electromagnetic radiation according to the present invention). According to the present invention, the carrier substrate may be at least opaque to the wavelength of the laser by coupling the laser beam to the substrate stack (product substrate-carrier substrate junction), particularly when functional (metal) substrate units and / or ridge structures are present. The carrier substrate is preferably selected from a material that does not attenuate the intensity of the laser beam to any significant degree.

[0051] The carrier substrate is mainly composed of one or more of the following materials:

[0052] o glass

[0053] o Minerals, especially sapphire

[0054] o Semiconductor materials, especially silicon

[0055] o Polymer

[0056] o Composite materials

[0057] According to the present invention, glass is a preferred material for the carrier substrate.

[0058] The thickness of the carrier substrate is selected to be sufficiently large to ensure that the product substrate is sufficiently stable (especially in relation to the connection layer).

[0059] The thickness of the carrier substrate is greater than 100 μm, preferably greater than 500 μm, more preferably greater than 1000 μm, most preferably greater than 1500 μm, and most preferably greater than 2000 μm.

[0060] At the same time, the thickness is selected to be as thin as possible so that the intensity of the laser beam is selected to be as small as possible. The thickness of the carrier substrate is less than 2000 µm, preferably less than 1750 µm, more preferably less than 1500 µm, most preferably less than 1250 µm, and most preferably less than 900 µm.

[0061] Connecting layer, especially bonding adhesive

[0062] The bonding adhesive is specifically selected from one or more of the following materials:

[0063] Polymers, especially

[0064] o Inorganic polymer, preferably

[0065] ■ Polyphosphazene,

[0066] ■ Polysiloxane, Silicone,

[0067] ■ Polysilane,

[0068] o Organic polymers, especially

[0069] ■ Acrylic ester styrene acrylonitrile,

[0070] ■ Acrylonitrile / methyl metalylate,

[0071] ■ Acrylonitrile / Butadiene / Acrylate,

[0072] ■ Acrylonitrile / chlorinated, polyethylene / styrene,

[0073] ■ Acrylonitrile-butadiene-styrene,

[0074] ■ Acrylic polymer,

[0075] ■ Alkyd resin,

[0076] ■ Butadiene rubber,

[0077] ■ Butyl rubber,

[0078] ■ Casein plastic, artificial horn,

[0079] ■ Cellulose acetate,

[0080] ■ Cellulose esters and derivatives,

[0081] ■ Cellulose hydrate,

[0082] ■ Cellulose nitrate,

[0083] ■ Chitin, Chitosan,

[0084] ■ Chloroprene rubber,

[0085] ■ Cyclo-olefin copolymer,

[0086] ■ Standardized polyvinyl chloride,

[0087] ■ Epoxy resin,

[0088] ■ Ethylene ethyl acrylate copolymer

[0089] ■ Ethylene polyvinyl acetate,

[0090] ■ Ethylene propylene copolymer,

[0091] ■ Ethylene propylene diene rubber,

[0092] ■ Ethylene vinyl acetate,

[0093] ■ Expandable polystyrene,

[0094] ■ Fluorinated rubber,

[0095] ■ We formaldehyde resin,

[0096] ■ Urea resin,

[0097] ■ Isoprene rubber,

[0098] ■ Melamine formaldehyde resin,

[0099] ■ Melamine resin,

[0100] ■ Methyl Acrylate / Butadiene / Styrene,

[0101] ■ Natural rubber,

[0102] ■ Perfluoroalkoxyalkanes,

[0103] ■ Phenol formaldehyde resin,

[0104] ■ Polyacetal,

[0105] ■ Polyacrylonitrile,

[0106] ■ Polyamide,

[0107] ■ Polybutylene succinate,

[0108] ■ Polybutylene terephthalate,

[0109] ■ Polycaprolactone,

[0110] ■ Polycarbonate,

[0111] ■ Polychlorotrifluoroethylene,

[0112] ■ Polyester,

[0113] ■ Polyesteramide,

[0114] ■ Polyester alcohol,

[0115] ■ Polyester block amide,

[0116] ■ Polyester imide,

[0117] ■ Polyester ketone,

[0118] ■ Polyester sulfone,

[0119] ■ Polyester ethylene,

[0120] ■ Polyester terephthalate,

[0121] ■ Polyhydroxyalkanonate,

[0122] ■ Polyhydroxybutyrate,

[0123] ■ Polyimide,

[0124] ■ Polyisobutylene,

[0125] ■ Polylactide,

[0126] ■ Polymethacrylmethylimide,

[0127] ■ Polymethyl metalylate,

[0128] ■ Polymethylpentine,

[0129] ■ Polyoxymethylene or polyacetal,

[0130] ■ Polyphenyl ether,

[0131] ■ Polyphenyl sulfide,

[0132] ■ Polyphthalamide,

[0133] ■ Polypropylene,

[0134] ■ Polypropylene copolymer,

[0135] ■ Polypyrrole,

[0136] ■ Polystyrene,

[0137] ■ Polysulfone,

[0138] ■ Polytetrafluoroethylene,

[0139] ■ Polytrimethylene terephthalate,

[0140] ■ Polyurethane,

[0141] ■ Polyvinyl acetate,

[0142] ■ Polyvinyl butyral,

[0143] ■ Polyvinyl chloride (rigid PVC),

[0144] ■ Polyvinyl chloride (flexible PVC),

[0145] ■ Polyvinylidene fluoride,

[0146] ■ Polyvinyl pyrrolidone,

[0147] ■ Styrene acrylonitrile copolymer,

[0148] ■ Styrene butadiene rubber,

[0149] ■ Styrene Butadiene Styrene,

[0150] ■ Synthetic rubber,

[0151] ■ Thermoplastic polyurethane,

[0152] ■ Unsaturated polyester,

[0153] ■ Vinyl acetate copolymer,

[0154] ■ Vinyl chloride / ethylene / methacrylate,

[0155] ■ Vinyl chloride / ethylene,

[0156] ■ Vinyl chloride vinyl acetate copolymer,

[0157] ■ Softened polyvinyl chloride.

[0158] Above all, all inorganic polymers such as silicon have relatively high transparency over a wide wavelength range of the laser as a radiation source (preferred laser according to the present invention), and therefore, according to the present invention, are preferably used as bonding adhesives.

[0159] The bonding adhesive is preferably applied by the following process steps: In the first process step, the bonding adhesive is applied by a spin-coating process. In the second process step, heat treatment is performed to remove any solvent. The temperature of the heat treatment is particularly greater than 50°C, preferably greater than 75°C, more preferably greater than 100°C, most preferably greater than 100°C, and most preferably greater than 150°C. Preferably, the temperature of the heat treatment is less than 500°C.

[0160] availability layer

[0161] The soluble layer may be composed of any random material, one or more sides of the soluble layer, preferably lead with sides facing the product substrate, to reduce adhesion under the influence of the aforementioned electromagnetic radiation. The soluble layer according to the present invention completely sublimes, particularly under the influence of electromagnetic radiation.

[0162] In a specific embodiment according to the present invention, the soluble layer may be composed of a laminate foil.

[0163] The soluble layer according to the present invention is preferably composed of or applied as a molecular layer, particularly a mono-layer. In particular, the layer thickness of the soluble layer according to the present invention is less than 100 μm, preferably less than 50 μm, more preferably less than 10 μm, most preferably less than 500 nm, and most preferably less than 1 nm.

[0164] The physical and / or chemical properties of the soluble layer in relation to electromagnetic radiation are selected particularly at least partially, preferably primarily, and more preferably completely to complement the corresponding physical and / or chemical properties and / or settings (particularly by the setting of parameters such as pressure, humidity, and temperature) of the connecting layer and / or carrier substrate (particularly by material selection). The affecting electromagnetic radiation is completely absorbed at least primarily by the soluble layer according to the present invention.

[0165] The absorption of electromagnetic radiation, particularly photons, by the soluble layer according to the present invention is particularly greater than 50%, preferably greater than 75%, more preferably greater than 90%, most preferably greater than 99%, and most preferably greater than 99.9%. Accordingly, the transmission may be less than 50%, preferably less than 25%, more preferably less than 10%, most preferably less than 1%, and most preferably less than 0.1%. Here, the absorption value is set for a layer thickness selected according to the requirements of the product wafer and material properties.

[0166] The material of the soluble layer and electromagnetic radiation are selected such that, due to the interaction between the electromagnetic radiation and the soluble layer, the maximum possible number of rotational and / or vibrational degrees of freedom is excited and / or the maximum possible number of electrons move from the highest occupied molecular orbital to the lowest occupied molecular orbital. Preferably, the interaction is performed particularly entirely in the UV-VIS spectrum. Consequently, there is a direct effect on the electronic structure, and there is no excitation of rotational and / or vibrational degrees of freedom. The excitation of rotational and / or vibrational degrees of freedom induces heating of the soluble layer according to the present invention and consequently heating of the adjacent product substrate.

[0167] The material of the soluble layer and the electromagnetic radiation are selected such that the temperature increase of the soluble layer due to interaction with the electromagnetic radiation is less than 50°C, less than 25°C, more preferably less than 10°C, most preferably less than 1°C, and most preferably less than 0.1°C. The use of a photon source having an electromagnetic wavelength range that does not excite vibrational or rotational degrees of freedom can be particularly excluded for heating. Therefore, to prevent heating, according to the present invention, all electromagnetic rays in the UV-VIS wavelength range are used.

[0168] Appropriate heating of the soluble layer according to the present invention may be desirable, because the breakdown of the soluble layer according to the present invention is promoted by an increase in thermal motion. The heating is at least 0.1°C, at least 1°C, at least 5°C, and more preferably 10°C.

[0169] Materials considered suitable as a soluble layer specifically fall under the following:

[0170] Polymers, especially

[0171] o Organic polymers, especially

[0172] ■ Acrylic ester styrene acrylonitrile,

[0173] ■ Acrylonitrile / methyl metalylate,

[0174] ■ Acrylonitrile / Butadiene / Acrylate,

[0175] ■ Acrylonitrile / chlorinated, polyethylene / styrene,

[0176] ■ Acrylonitrile-butadiene-styrene,

[0177] ■ Acrylic polymer,

[0178] ■ Alkyd resin,

[0179] ■ Butadiene rubber,

[0180] ■ Butyl rubber,

[0181] ■ Casein plastic, artificial blend.

[0182] ■ Cellulose acetate,

[0183] ■ Cellulose esters and derivatives,

[0184] ■ Cellulose hydrate,

[0185] ■ Cellulose nitrate,

[0186] ■ Chitin, Chitosan,

[0187] ■ Chloroprene rubber,

[0188] ■ Cycloolefin copolymer,

[0189] ■ Standardized polyvinyl chloride,

[0190] ■ Epoxy resin,

[0191] ■ Ethylene ethyl acrylate copolymer

[0192] ■ Ethylene polyvinyl acetate,

[0193] ■ Ethylene propylene copolymer,

[0194] ■ Ethylene propylene diene rubber,

[0195] ■ Ethylene vinyl acetate,

[0196] ■ Expandable polystyrene,

[0197] ■ Fluorinated rubber,

[0198] ■ Urea formaldehyde resin,

[0199] ■ Urea resin,

[0200] ■ Isoprene rubber,

[0201] ■ Lignin,

[0202] ■ Melamine formaldehyde resin,

[0203] ■ Melamine resin,

[0204] ■ Methyl Acrylate / Butadiene / Styrene,

[0205] ■ Natural rubber,

[0206] ■ Perfluoroalkoxyalkanes,

[0207] ■ Phenol formaldehyde resin,

[0208] ■ Polyacetal,

[0209] ■ Polyacrylonitrile,

[0210] ■ Polyamide,

[0211] ■ Polybutylene succinate,

[0212] ■ Polybutylene terephthalate,

[0213] ■ Polycaprolactone,

[0214] ■ Polycarbonate

[0215] ■ Polycarbonates,

[0216] ■ Polychlorotrifluoroethylene,

[0217] ■ Polyester,

[0218] ■ Polyesteramide,

[0219] ■ Polyester alcohol,

[0220] ■ Polyester block amide,

[0221] ■ Polyester imide,

[0222] ■ Polyester ketone,

[0223] ■ Polyester sulfone,

[0224] ■ Polyethylene,

[0225] ■ Polyester terephthalate,

[0226] ■ Polyhydroxyalkanoates,

[0227] ■ Polyhydroxybutyrate,

[0228] ■ Polyimide,

[0229] ■ Polyisobutylene,

[0230] ■ Polylactide,

[0231] ■ Polymethacrylmethylimide,

[0232] ■ Polymethyl metalylate,

[0233] ■ Polymethylpentine,

[0234] ■ Polyoxymethylene or polyacetal,

[0235] ■ Polyphenyl ether,

[0236] ■ Polyphenyl sulfide,

[0237] ■ Polyphthalamide,

[0238] ■ Polypropylene,

[0239] ■ Polypropylene copolymer,

[0240] ■ Polypyrrole,

[0241] ■ Polystyrene,

[0242] ■ Polysulfone,

[0243] ■ Polytetrafluoroethylene,

[0244] ■ Polytrimethylene terephthalate,

[0245] ■ Polyurethane,

[0246] ■ Polyvinyl acetate,

[0247] ■ Polyvinyl butyral,

[0248] ■ Polyvinyl chloride (rigid PVC),

[0249] ■ Polyvinyl chloride (flexible PVC),

[0250] ■ Polyvinylidene fluoride,

[0251] ■ Polyvinyl pyrrolidone,

[0252] ■ Styrene acrylonitrile copolymer,

[0253] ■ Styrene butadiene rubber,

[0254] ■ Styrene Butadiene Styrene,

[0255] ■ Synthetic rubber,

[0256] ■ Thermoplastic polyurethane,

[0257] ■ Unsaturated polyester,

[0258] ■ Vinyl acetate copolymer,

[0259] ■ Vinyl chloride / ethylene / methacrylate,

[0260] ■ Vinyl chloride / ethylene,

[0261] ■ Vinyl chloride vinyl acetate copolymer,

[0262] ■ Softened polyvinyl chloride.

[0263] o Inorganic polymer

[0264] ■ Polyphosphazene

[0265] ■ Polysiloxane, Silicone

[0266] ■ Polysilane

[0267] Metals, especially Cu, Ag, Au, Al, Fe, Ni, Co, Pt, W, Cr, Pb, Ti, Ta, Zn, and Sn

[0268] metal alloy

[0269] nonmetal

[0270] o Ceramic

[0271] o glass

[0272] ■ Metallic glass

[0273] ■ Non-metallic glass, especially

[0274] Organic non-metallic glass

[0275] Inorganic non-metallic glass, especially

[0276] o Non-oxidized glass, especially

[0277] ■ Halide Glass

[0278] ■ Chalcogenide glass

[0279] o Oxide glass, especially

[0280] ■ Phosphate glass

[0281] ■ Silicate leaf glass, especially

[0282] Aluminosilicate glass

[0283] lead-silicate glass

[0284] Alkali-silicate glass, especially

[0285] o Alkaline and alkaline earth silicate glass

[0286] Borosilicate glass

[0287] Borate glass, especially alkali borate glass

[0288] According to the present invention, a soluble layer from the polymer is preferably used.

[0289] This polymer is suitable as a soluble layer due to numerous bonding types, particularly sigma bonds, Pi bonds, and resonance-stabilized aromatic compound bonds (benzene rings). These bonds generate a significantly complex UV-VIS spectrum, within which a wavelength range occurs where resonance interactions begin to take place between incident photons and electrons. Metals and metal alloys possess the absorption spectrum of crystalline solids. Metals and metal alloys can be heated via photon excitation and are suitable as soluble layers. Ceramics and glass exhibit minimal interaction effects. They are mostly amorphous or at least partially amorphous.

[0290] The soluble layer is preferably applied using the following process steps: In the first process step, the soluble layer is applied by a spin-coating process. In the second process step, heat treatment is performed to remove any solvent. The temperature of the heat treatment is particularly greater than 50°C, preferably greater than 75°C, more preferably greater than 100°C, most preferably greater than 100°C, and most preferably greater than 150°C. Preferably, the temperature of the heat treatment is less than 500°C.

[0291] In the third process step, the second heat treatment is performed at a high temperature to cure the soluble layer. The heat treatment temperature is particularly greater than 100°C, preferably greater than 150°C, more preferably greater than 200°C, most preferably greater than 250°C, and most preferably greater than 300°C. Curing can also be performed by electromagnetic radiation, particularly UV light. Chemical curing is performed using a process gas. In particular, curing can be performed using air humidity.

[0292] In the first embodiment according to the present invention, the substrate stack (product substrate-to-carrier substrate bond) comprises a product substrate, a soluble layer of the present invention applied to the entire surface of the product substrate, a bonding adhesive (connecting layer), and a carrier substrate.

[0293] The surface of the product substrate is not flat. In addition, there is a functional unit having a raised structure on the upper side of the coated product substrate.

[0294] According to the present invention, this type of substrate stack can be manufactured in one or more of the process steps described below.

[0295] In the first process step according to the present invention, the entire surface of the product substrate, in particular, is coated with the soluble layer of the present invention. The coating of the soluble layer of the present invention may be performed by blanket coating, spray coating, or spin coating (preferred). If the soluble layer of the present invention is a foil, it is preferably laminated.

[0296] In the second process step according to the present invention, a bonding adhesive (connecting layer) is applied. The bonding adhesive may be applied onto the soluble layer, product substrate, and / or carrier substrate of the present invention.

[0297] In the third process step according to the present invention, two substrates are bonded together (in particular, in contact with each other under pressure). An alignment process may be performed prior to bonding.

[0298] In a second embodiment according to the present invention, the substrate stack (product substrate-to-carrier substrate bond) comprises a product substrate, a non-adhesive coating applied to the center of the product substrate, a soluble layer of the present invention applied to the periphery, a bonding adhesive (connecting layer), and a carrier substrate.

[0299] According to the present invention, this type of substrate stack is manufactured particularly by one or more process steps described below:

[0300] In the first process step according to the present invention, the product substrate is concentrically coated with a non-adhesive coating. The non-adhesive coating may be applied by spin-coating or spray-coating. The non-adhesive coating is not applied over the entire surface. In particular, the periphery ring is kept uncoated, and the ring width is less than 10 mm, preferably less than 5 mm, more preferably less than 3 mm, most preferably less than 2 mm, and most preferably less than 1 mm. To obtain a central coating having an uncoated periphery ring, the product substrate is masked over the area of ​​the periphery ring.

[0301] In the second process step according to the present invention, the peripheral ring of the product substrate is coated with the soluble layer of the present invention. The coating of the soluble layer of the present invention is performed by spin coating, spray coating, or blanket coating. If the soluble layer of the present invention is a foil, it is preferably laminated in the peripheral area. Full-surface lamination and removal of the foil may also be implemented.

[0302] In the third process step according to the present invention, a bonding adhesive is applied. The bonding adhesive may be applied to a soluble layer, thereby to a product substrate and / or a carrier substrate.

[0303] In the fourth process step according to the present invention, two substrates are bonded together (especially in contact with each other under pressure). An alignment process may be performed prior to bonding.

[0304] The influence on the soluble layer (by electromagnetic radiation) of the present invention is concentrated in the surroundings or entirely influenced from the side.

[0305] Alternatively, affecting the solubility layer of the present invention of the substrate stack can be achieved by using the plant mentioned in PCT / EP2015 / 050607.

[0306] In a third embodiment according to the present invention, the substrate stack consists of a product substrate, a bonding adhesive, a non-adhesive layer applied at the center of the carrier substrate, and a soluble layer of the present invention applied around it. This embodiment is an extension of US20090218560A1 of this specification.

[0307] Deboning operation

[0308] Prior to the release operation according to the present invention, the product substrate is preferably fixed to a film clamped to a film frame. The film frame and the film stabilize the relatively thin product substrate after the carrier substrate is removed. The carrier substrate is preferably not removed until the product substrate is applied to the film attached to the film frame.

[0309] The release process is preferably performed by a laser. The laser reduces the bonding strength / force between the carrier substrate and the bonding adhesive according to the third embodiment of the present invention / the product substrate and the connecting layers according to the first embodiment of the present invention. The bonding strength / force is reduced particularly by more than 50%, preferably more than 75%, and more preferably more than 90%.

[0310] In accordance with the release of the substrate stack according to the present invention, the second and third embodiments may be carried out in a plant particularly as described in Publication No. PCT / EP2015 / 050607.

[0311] After the debonding process, the surface of the product substrate is preferably cleaned. In a further major aspect according to the present invention, the complete removal of the soluble layer according to the first embodiment of the present invention results in a product substrate having a relatively clean surface, and the cleaning thereof is faster and more cost-effective.

[0312] Insofar as features related to the method are disclosed, they are deemed to be disclosed to the device as well, and vice versa. Brief explanation of the drawing

[0313] FIG. 1a is a schematic drawing (not scale) of a first embodiment of a product substrate-to-carrier substrate joint of the present invention. FIG. 1b is a schematic diagram (not scale) of an embodiment of the method of the present invention for separating a product substrate-to-carrier substrate junction according to FIG. 1a. FIG. 2a is a schematic drawing (not scale) of a second embodiment of a product substrate-to-carrier substrate joint of the present invention. FIG. 2b is a schematic diagram (not scale) of an embodiment of the method of the present invention for separating a product substrate-to-carrier substrate junction according to FIG. 2a. FIG. 3 is a schematic drawing (not scale) of a third embodiment of a product substrate-to-carrier substrate joint of the present invention. FIG. 4 is a schematic diagram (not scaled) of the first absorption graph (adsorption = absorption). Figure 5 is a schematic diagram (not scaled) of the second absorption graph (adsorption = absorption). Specific details for implementing the invention

[0314] In the drawings, identical or functionally identical components are depicted with the same reference numeral.

[0315] All illustrated product substrates (2) may include a functional unit (6). However, if possible, there are also product substrates that do not include a corresponding functional unit (6). The functional unit (6) may be, for example, a microchip, a storage module, a MEM component, etc. The functional unit (6) may also include a raised structure (7), such as a solder ball. Such raised structures (7) may have different shapes, and thus it is difficult and / or incomplete to coat these structures with a soluble layer (3). With respect to the coating of the product substrate (2), this includes coating of the functional unit (6) and / or the raised structure (7).

[0316] FIG. 1a illustrates a schematic first embodiment of the present invention of a substrate stack (1) comprising at least one product substrate (2), a soluble layer (3), a bonding adhesive such as a connecting layer (4), and a carrier substrate (5) (not scale). The soluble layer (3) of the present invention is applied to the top of the provided product substrate (2) having its (potential) functional unit (6) and ridge structure (7), particularly to the entire surface. The surface of the soluble layer (3o) is in contact with the bonding adhesive that is connected in turn to the carrier substrate (5).

[0317] FIG. 1b illustrates a schematic diagram (not scaled) of a separation operation according to the present invention. A laser (9) generates a laser beam (10) that penetrates into the bonding adhesive through a carrier substrate (5). According to the present invention, absorption by the bonding adhesive is minimized due to the synchronization of the wavelength of the laser beam (10) of the present invention. Therefore, the laser beam (10) proceeds into the soluble layer (3) with particularly minimal, and more preferably negligibly low, energy loss.

[0318] According to the present invention, the interaction between the photons of the soluble layer (3) and the laser beam (10) is significantly greater than that using a bonding adhesive, and preferably maximum. The soluble layer (3) is at least partially, preferably predominantly, and more preferably completely dissolved or destroyed. The adhesive strength between the product substrate (2) and the bonding adhesive is at least reduced.

[0319] The laser (9) scans the entire surface (3o) of the soluble layer, particularly by moving in the x-direction and / or y-direction. Unless the laser beam (10) is optimally parallelized, it is also possible to move the laser beam (10) in the z-direction to ensure better focusing.

[0320] FIG. 2a comprises at least one product substrate (2), a soluble layer (3) applied entirely around the product substrate (2), a non-adhesive layer (8) applied centrally to the product substrate (2), a connecting layer (4) composed of a bonding adhesive, and a carrier substrate (5). In a state where the adhesive strength existing between the soluble layer (3) and the bonding adhesive of the present invention is relatively high (at least twice as high), the adhesive effect between the non-adhesive layer (8) and the bonding adhesive is minimized according to the present invention.

[0321] FIG. 2b illustrates the collapse of the soluble layer (3) of the second embodiment of the present invention shown in FIG. 2a. The laser beam (10) is preferably focused on the periphery of the substrate stack (1'). Preferably, the plant is designed so that the laser (9) is fixed and the substrate stack (1') rotates around the rotation axis (R).

[0322] FIG. 3 illustrates a schematic third embodiment of the present invention (not scale) of a substrate stack (1') according to the present invention, which comprises at least one product substrate (2), a connecting layer (4) composed of a bonding adhesive, a flexible layer (3) applied entirely around a carrier substrate (5), a non-adhesive layer (8) applied centrally to a carrier substrate (5), and a carrier substrate (5).

[0323] The soluble layer (3) is applied around the carrier substrate (5), and the soluble layer (3) is sensitive to the wavelength of the laser beam (10) used. The separation operation is performed by the configuration of the embodiment of the invention shown in FIG. 2b or by the plant disclosed in PCT / EP2015 / 050607.

[0324] FIG. 4 illustrates an absorption graph (11) of a cutout of the absorption spectrum of a bonding adhesive. The absorption spectrum is, in particular, a UV-VIS absorption spectrum. The absorption graph (11) preferably has at least one, particularly more than two, more preferably more than three, most preferably more than four, most preferably more than five local absorption minimums (12).

[0325] For clarity, only one local absorption minimum (12) is plotted at the center of the absorption graph (11). The local absorption minimum (12) is part of the optimal absorption region (13), and the wavelength of the laser beam (10) of the laser (9) to be used according to the present invention is adjusted to match that wavelength range.

[0326] According to the present invention, the bonding adhesive used is selected such that the wavelength of the laser beam (10) used is within the optimal absorption region (13), preferably exactly matching the minimum absorption value (12). In this way, the bonding adhesive for the laser beam (10) is ensured to have maximum transparency according to the present invention.

[0327] FIG. 5 illustrates an absorption graph (11') of a cutout of the absorption spectrum of the soluble layer (3). The absorption spectrum is, in particular, a UV-VIS absorption spectrum. The absorption graph (11') preferably contains at least one, particularly more than two, more preferably more than three, most preferably more than four, and most preferably more than five absorption maximums (14). For clarity, only two local absorption maximums (14) are shown in the absorption graph (11').

[0328] The local absorption maximum value (14) is part of the optimal absorption region (13'), and the wavelength of the laser beam (10) of the laser (9) used must be adjusted to match that wavelength range. According to the present invention, a soluble layer (3) is selected so that the wavelength of the laser beam (10) used is within the optimal absorption region (13'), preferably so as to exactly match the absorption maximum value (14). In this way, according to the present invention, the absorption of the soluble layer for the laser beam (10) is ensured to be maximized.

[0329] According to the present invention, it is critically important that the soluble layer (3) is reached entirely by the laser beam (10) to a remarkable degree. Unless the wavelengths of the laser beam (10) of the bonding adhesive (4) and the soluble layer (3) cannot be optimally adjusted to each other, preferably, the wavelength of the laser beam (10) should be adjusted to match one or more absorption minimums of the bonding adhesive so as to allow photons of the laser beam (10) to access the soluble layer (3) without hindrance. Explanation of the symbols

[0330] 1, 1', 1" board stack (product board-to-carrier board bonding) 2 Product Board 3 Availability Layers 3o Surface of the soluble layer 4 connection layers 5 Carrier Substrate 5o surface of the carrier substrate 6 Function Units 7 Uplifted structures 8 non-stick layers 8o surface of the non-stick layer 9 Laser 10 laser beams 11 Absorption Graph 12 minimum absorption value 13 Optimal absorption area 14 Maximum absorption value 15 Availability Layers R rotation axis

Claims

Claim 1 A method for bonding a product substrate (2) to a carrier substrate (5) through a connecting layer (4), wherein a soluble layer (3) is applied on the product substrate (2), and the connecting layer (4) is applied such that the soluble layer (3) is disposed between the connecting layer (4) and the product substrate (2), wherein a) the soluble layer (3) is made soluble by interaction with electromagnetic radiation of a laser, and b) the connecting layer (4) and the carrier substrate (5) each have permeability to the electromagnetic radiation, and the laser can be operated in a pulsed mode. Claim 2 A method for separating a product substrate (2) from a carrier substrate (5) bonded to a product substrate (2) through a connecting layer (4), wherein a soluble layer (3) is applied on the product substrate (2), and the connecting layer (4) is applied such that the soluble layer (3) is disposed between the connecting layer (4) and the product substrate (2), wherein a) the soluble layer (3) is dissolved by interaction with electromagnetic radiation of a laser, and b) the connecting layer (4) and the carrier substrate (5) each have permeability to the electromagnetic radiation, and the laser can be operated in a pulsed mode. Claim 3 A method according to claim 1 or 2, wherein the physical and / or chemical properties of the soluble layer with respect to electromagnetic radiation are selected to be complementary to the corresponding physical and / or chemical properties of the connecting layer (4) and / or the carrier substrate (5). Claim 4 A method according to claim 1 or 2, wherein the photon absorption of the electromagnetic radiation in the connecting layer (4) is less than 50%. Claim 5 A method according to claim 1 or 2, wherein the photon absorption of the electromagnetic radiation in the soluble layer (3) is greater than 50%. Claim 6 A method according to claim 1 or 2, wherein the connecting layer (4) is heated to less than 50°C during separation. Claim 7 A method according to claim 1 or 2, wherein the soluble layer (3) is sublimated by the electromagnetic radiation. Claim 8 A method according to claim 1 or 2, wherein the soluble layer (3) is composed of or applied with a layer thickness of less than 10 μm. Claim 9 A product substrate-carrier substrate joint comprising a product substrate (2) bonded to a carrier substrate (5) by a connecting layer (4), wherein a soluble layer (3) is disposed between the connecting layer (4) and the product substrate (2), and the soluble layer (3) is applied directly to the product substrate (2), wherein a) the soluble layer (3) becomes soluble upon interaction with electromagnetic radiation of a laser, and b) each of the connecting layer (4) and the carrier substrate (5) has permeability to electromagnetic radiation transmitted through the connecting layer (4), and the laser can be operated in a pulsed mode.

Citation Information

Patent Citations

  • Light receiving element and its manufacturing method

    JP2004319543A

  • Method of transferring device and method of manufacturing display apparatus

    JP2010177390A

  • Laminated body and method for separating laminated body

    JP2012106486A

  • Laminated body, method of preparing the same, and method of fabricating electronic device using said laminated body

    JP2015104843A

  • Method of transferring a device and method of manufacturing a display apparatus

    US20100186883A1